EKSPRESI WAJAH DALAM KARYA LUKIS - KHAIRUL MAHMUD, Yasrul Sami, S.Sn., M.Sn., Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2017)
The purpose of creating a painting is to describe the human facial expressions such as feelings of sadness, fear, disappointment, threat, happiness, happiness, emotion, pain, distress, surprise and other expressions. Methods in realizing the idea of art include: preparation, elaboration, synthesis, realization and completion. The results of the discussion is that humans have the nature as a social creature, so that humans are required to interact with each other to establish a harmonious life in the community.Keywords: Facial expressions, Art